PENGARUH STRUKTUR KEPEMILIKAN, STRUKTUR MODAL, PROFITABILITAS DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Tomi Yuniardi M, 12.05.52.0120; Sunarto, Sunarto (Students' Journal of Accounting and Banking, 2016)
The study examines the effect of structure ownership, institutional ownership, financial capital structure, profitability, growth of company toward firm value. This research was conducted at the Indonesian Stock Exchange by using go public manufacturing company as the unit of analysis. The sampling method used purposive sampling with a sample of 160 objeck of companies listed on the Indonesian Stock Exchange in the period is 2010 until 2014. Analysis instrument used  multiple regression analysis. The results showed that the profitability has positive effect and significant to the corporate value. Whereas the structure ownership, institutional ownership, financial capital structure and growth of company had no significant effect on firm value.Keywords: Ownership Structure, Ownership Institutional, Financial Capital Structure, Profitability, Growth of Company and Firm Value